Optimalization of Instagram Features in Developing Digital Marketing Strategies: A Case Study of Bersama Outdoor Rent - Mahmuddin; Pahrul (Cita konsultindo, 2025)
This study examines the optimization of Instagram features as a digital marketing strategy for Bersama Outdoor Rent, an SME operating in the outdoor equipment rental and adventure service sector. Using a qualitative case study design, data were collected through in-depth interviews, direct observation of the Instagram account, and analysis of supporting documentation. The findings reveal that Instagram features are utilized unevenly; Feed posts and Direct Messages are optimized effectively for visual branding and transactional communication, while other features such as Stories, Highlights, hashtags, and especially Reels remain underutilized. The lack of structured content planning, irregular updates, and limited analytics-based evaluation hinder the business from achieving broader reach and higher engagement. These results highlight that effective digital marketing on Instagram requires strategic planning, systematic feature integration, and consistent performance monitoring. The study provides practical insights for SMEs seeking to maximize Instagram’s potential as a primary digital marketing platform.